Applying human-centered design principles to climate services in Nairobi, Kenya: Workshop Report - Giraldo Mendez, Diana Carolina; Zapata Caldas, Emmanuel; Ortiz Crespo, Berta; Simiyu, Maryfaith; Muller, Anna (2024)
The workshop, held on November 29th and 30th, 2023, in Nairobi, Kenya, was designed for EiA use cases currently working with or planning to work with climate data and services, as well as for teams developing and delivering climate services. During this initial workshop, we applied exploratory methods based on HCD principles to better understand users and providers, examine use cases, define objectives, and establish desired outcomes for the playbook. We also explored how the playbook could enhance decision-making in the implementation of climate services while addressing specific challenges within EiA use cases. The workshop objectives were: (i) to understand the needs of the participants in order to identify the gaps that the guiding document or playbook should address; (ii) to examine how climate services are currently implemented and the major challenges faced by organizations; and (iii) to gather assumptions about end-users of climate services, including how they perceive and interact with them.